Brand awareness, brand preference, and brand loyalty of sport apparel amongst select ethnic groups / Karen E. Danylchuk and David C. Sit - Danylchuk, Karen E.; Sit, David C. (Faculty of Sports Science and Recreation, 2005)
Sport consumers are overwhelmed by choice and marketers have addressed this problem by differentiating their products or services through branding. However, understanding consumers is difficult for marketers because of the increasing variety of consumers' ethnic origins. This study investigated whether there are branding differences amongst select ethnic groups in Canada. A study of 338 consumers of Chinese, East Indian, and Anglo- European ethnicity was conducted using the shopping mall intercept approach. Participants were asked to rate 14 brand awareness factors, 14 brand preference factors, and 11 brand loyalty factors in relation to sport apparel brands. A supplementary study was conducted to investigate whether three predominant sport apparel companies employ different marketing strategies for specific ethnic groups in Canada. Multivariate and univariate analyses of variance determined that there were significant differences for only six of the 39 branding factors amongst the three ethnic groups. These differences occurred more frequently between the East Indians and Anglo-Europeans. Analyzing for differences with the demographic variables (sex, age, years lived in Canada, occupational status, generational status, level of education, and income) independently showed branding differences for all factors except income. When both the ethnicity and sub-group analyses were considered, most differences were found with brand awareness and preference for sport apparel brands. Results also indicated that the three predominant sport apparel brands do not participate in ethnic marketing in Canada; their two major focuses are marketing to the masses and segmenting by age groups.